2020
DOI: 10.1088/1757-899x/713/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Improvement for significant clauses in the standard form of contract for industrialized building system construction

Abstract: Industrialized Building System (IBS) has been introduced in Malaysia since the 1960s. The government has come out with varies strategic blueprint to push IBS as a national agenda. Unfortunately, the pace of adaptation of IBS is still slow and below the government’s target. Construction players are still facing various issues when adopting IBS particularly on contractual and procurement aspects; thus it contributes to the low adoption of IBS in Malaysia. Lack of provision in the Malaysia standard form of contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Besides, sustainability and generating economic turnover were some of the obstacles mentioned in the industry (Shamsuddin et al, 2018). Moreover, there is also a suggestion to review the existing standard form of contract to suit the IBS system in Malaysia (Fateh et al, 2020). This suggestion was previously asserted by H. L. T. Ariffin et al (2019) on the importance of having dedicated procurement specialised in IBS.…”
Section: Issues and Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, sustainability and generating economic turnover were some of the obstacles mentioned in the industry (Shamsuddin et al, 2018). Moreover, there is also a suggestion to review the existing standard form of contract to suit the IBS system in Malaysia (Fateh et al, 2020). This suggestion was previously asserted by H. L. T. Ariffin et al (2019) on the importance of having dedicated procurement specialised in IBS.…”
Section: Issues and Problemsmentioning
confidence: 99%
“…29 (1): 635 -652 ( 2021) key players (Nasrun & Nawi, 2015) and investigating factors of delays (Nawi et al, 2019) . In summary, issues and problems can be categorised into procurement (Fateh et al, 2020) management (Fauzi et al, 2017;Noor et al, 2018); and system (Ern et al, 2017;Md. Ali et al, 2018;Razak & Awang, 2014).…”
Section: Issues and Problemsmentioning
confidence: 99%
“…Salah satu dari teknologi yang semakin berkembang dan mendapat perhatian dalam era IR 4.0 adalah teknologi Sistem Binaan Berindustri (IBS) yang merangkumi komponen pasang siap serta modular. Menurut Lembaga Pembangunan Industri Pembinaan Malaysia (CIDB), IBS secara umumnya dirujuk sebagai kaedah pembinaan di mana komponen dibina secara prasiap sama ada di tapak mahupun di kilang dan kemudiannya dipasang kepada struktur dengan kerja tambahan yang minimum [1]. Nawi et.…”
Section: Pengenalanunclassified
“…Design specifications put in place by the government, tend to stifle the element of creativity, during efforts to develop new construction methods, which may serve to reduce construction costs. The Construction Industry Development Board (CIDB) describes IBS as a construction approach, which involves the pre-fabrication of construction components at the plant, prior to their installation on the framework, with the least amount of required effort (Fateh et al, 2020). Rahim and Qureshi (2018) reported that the employment of the IBS approach shortened the construction duration, reduced the need for construction materials on-site, and improved the management of construction waste materials.…”
Section: The Monitoring Of Supplier Chargesmentioning
confidence: 99%